The repeated nomination as a unit of consistency category - Anorboyeva Iroda Oripovna (Research Parks Publishing LLC, 2021)
The repeated nomination in chain speech connected with primary nominations making a separate syntagmatic segment is considered in this article. Being different system languages parallel distinctions between French – Uzbek are expressed with spirit, custom and characteristic features of language norm